Shippey, Tom, trans., and Leonard Neidorf, ed. 2023. Beowulf: Translation and Commentary. London: Uppsala Books. Pp. ii + 418. ISBN 9781961361003. - Breeze, Andrew (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Review of Shippey, Tom, trans., and Leonard Neidorf, ed. 2023. Beowulf: Translation and Commentary. London: Uppsala Books. Pp. ii + 418. ISBN 9781961361003.